2018
DOI: 10.1021/acs.jpcc.8b00481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness and Adsorption of Airborne Hydrocarbons on Wetting Properties of MoS2: An Atomistic Simulation Study

Abstract: Molybdenum disulfide (MoS2) has attracted great attention due to its distinctive electronic, optical, chemical, and mechanical properties. In almost all of these applications, having a clear understanding about the wetting properties of MoS2 is essential. The basal plane of MoS2 has been generally believed to be hydrophobic with water contact angle (WCA) around 90°. Kozbial et al. have recently suggested that the freshly exfoliated MoS2 was intrinsically relative hydrophilic (WCA = 69.0 ± 3.8°); however, it co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…[ 44 ] Additional contamination source are airborne hydrocarbon contaminants adsorbing on the MoS 2 layers when exposed to air. [ 56,57 ] The device cleanliness can be improved by transfer strategies, which avoid the use of polymers. [ 58 ] However, such methods are not compatible with the large‐area transfer because the thin 2D material films without polymer support can cause uncontrolled transfer, leading to large cracks or folding in the transferred material.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 ] Additional contamination source are airborne hydrocarbon contaminants adsorbing on the MoS 2 layers when exposed to air. [ 56,57 ] The device cleanliness can be improved by transfer strategies, which avoid the use of polymers. [ 58 ] However, such methods are not compatible with the large‐area transfer because the thin 2D material films without polymer support can cause uncontrolled transfer, leading to large cracks or folding in the transferred material.…”
Section: Resultsmentioning
confidence: 99%
“…The aged MoS 2 basal plane (a simplified description including the effect of adsorbed airborne hydrocarbons), however, has a wide range of WCAs (73°–98°) recorded in the literature. , Because of this, we suggest picking the value of ε S that fits a specific experiment of interest with our “linear model”: where θ is in degrees and ε S is in kcal/mol. See Appendix for the proper range of θ and ε S where these equations apply.…”
Section: Resultsmentioning
confidence: 99%
“…For Lennard-Jones (LJ) interactions, we kept R min (= 2 1/6 σ), and ε Mo was the same from our previous study (Table ) and only optimized ε S to best fit the experimental WCAs. Thus, in contrast to the all-atom approach for an aged (or contaminated) surface, , we adopted a coarse-grained approach by adjusting ε S to include changes to WCA due to the adsorbed hydrocarbons. Instead of obtaining force-field parameters for each system with hydrocarbons and validating them using contact angle simulations, we directly fit force-field parameters to reproduce the experimental contact angles.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, a variety of water-MoS 2 contact angles have been experimentally determined in the literatures and it was found that the WCA closely depends on the surface aging conditions of MoS 2 and/or substrate materials (Gaur et al, 2014;Kozbial et al, 2015;Gurarslan et al, 2016). In previous studies (Govind Rajan et al, 2016;Leroy 2016;Heiranian et al, 2017;Sresht et al, 2017;Khalkhali et al, 2018), the WCA is always served as the dominated quantity to extract energy parameters of novel 2D nanomaterials, including the MoS 2 nanosheets here. For instance, through theoretical analysis and simulation, recent studies (Luan and Zhou, 2016;Zhang et al, 2019) have successfully reproduced the experimentally determined WCAs of the MoS 2 nanosheets under different conditions (Gaur et al, 2014;Kozbial et al, 2015;Gurarslan et al, 2016) by only modifying the Lennard-Jones parameter ε S (the depth of the potential well of a sulfur atom) and observed an excellent linear relationship between the ε S and WCAs.…”
Section: Derivation Of Energy Parameters For the Mos 2 Nanosheetsmentioning
confidence: 98%